EFEKTIVITAS LAYANAN KONSELING KELOMPOK TEKNIK SELF-MANAGEMENT UNTUK MENGURANGI PROKRASTINASI AKADEMIK - Rajafi, Haifa (Jurnal Psikoedukasia, 2023)
The purpose of this study was to see the effectiveness of group counseling with selfmanagement techniques to reduce academic procrastination of students in class X TKJ Harapan Mulya. The number of research samples consisted of 14 students. Sampling was determined by purposive sampling technique. In this study, the method used was the True Experimental Design method, the data analysis technique used Pre-Post Design. Based on the results of the analysis, it can be concluded that Group Counseling Self-Management Techniques can reduce the academic procrastination of students in class X TKJ SMK Harapan Mulya. This is based on the results of the t test, obtained t count = 5.774. While r table = 2.145. So group counseling services with self-management techniques are effective for reducing academic procrastination of class X TKJ students at SMK Harapan Mulya.